PELATIHAN SPORTPRENEUR DAN PENGEMBANGAN SPORT INDUSTRY 4.0 BAGI MAHASISWA OLAHRAGA DI KABUPATEN CIANJUR MENUJU PERTUMBUHAN EKONOMI ERA BARU - Adi Rahadian; Eneng Fitri Amalia; Asep Ramdan Afriyuandi; Muhamad Guntur Gaos Sungkawa; Andi Kurniawan Pratama; Purnama Mohammad Yasir Alansori; Muhammad Hifdi; Ilham Sani Tawakkal; Muhamad Tio Afrizal; Rima Marlina; Risda Pujayanti; Riri Ratna Lestari; Irwan Irwan; Beny Rustandi (MAJU : Indonesian Journal of Community Empowerment, 2026)
The sportpreneur training initiative, coupled with the promotion of the sports industry 4.0 within the student population of Cianjur Regency, signifies a crucial strategic endeavor aimed at augmenting the competencies, autonomy, and competitive edge of graduates from the PJKR Study Program in the framework of digital transformation and the green economy. This community service initiative is meticulously curated to equip students with indispensable knowledge, hands-on experience, and skill sets in technology-enabled sports entrepreneurship, which encompasses the deployment of digital platforms, data-driven marketing methodologies, and the innovation of sports-oriented products and services. The pedagogical approaches employed will encompass workshops, seminars, case analyses, mentorship, and practical applications in the formulation of sportpreneur business models that align with the contemporary needs of the sports industry. The projected outcomes of this initiative are to foster the emergence of innovative, technology-savvy young sports entrepreneurs who can significantly contribute to the growth of the sport industry 4.0 in Cianjur Regency. Consequently, the training is not solely intended to nurture sportpreneurs and enhance the capabilities of sports students but also possesses the capacity to catalyze new economic growth and facilitate the establishment of a sustainable regional sports industry ecosystem.